080 Obstructive sleep apnoea and atherosclerosis, vascular dysfunction and cardiac remodelling as assessed by CMR. (22nd September 2015) - Kylintireas, I K; Craig, S; Nethononda, R; Choudhury, R P; Stradling, J; Neubauer, S
Abstract : Objective: Obstructive sleep apnoea (OSA) is associated with hypertension, coronary artery disease, heart failure and stroke. We investigated whether OSA represents an additional independent risk factor for preclinical atherosclerosis, vascular dysfunction and cardiac remodelling as assessed by CMR. We also examined the effect of OSA severity as expressed by Oxygen Desaturation Index (ODI) on MR derived cardiac and vascular markers. Methods: In total, 58 patients with OSA and 39 control subjects without sleep apnoea underwent Cardiovascular Magnetic Resonance (CMR) scanning.42 OSA patients were meticulously matched for demographics, body size and cardiovascular risk factors to the 39 controls. CMR protocol: Our assessment included carotid and aortic atheroma burden quantification, central aortic distensibility assessment and left ventricular (LV) as well as right ventricular (RV) diastolic mass and volumes measurements. Multiple weighting, high resolution, imaging of the carotid vessels was used for carotid atheroma composition characterisation. Pulmonary artery (PA) acceleration time, a non invasive pulmonary artery pressure marker, was derived from velocity-encoded pulmonary artery flow imaging. Results: Carotid (p<0.05 (abstract 080 figure 1a )) and aortic (p<0.001 (abstract 080 figure1b )) wall thickness were increased in OSA patients in comparison with controls. Through multivariate regression analysis, ODI emerged as an independent predictor of both carotid (β=0.41(0.15)(p<0.01)) and aortic wall thickness (β=0.61(0.21)(p<0.01)). Carotid plaques, advanced carotid disease and "high risk" of carotid atheroma were all more prevalent among individuals suffering from OSA (p<0.05)(abstract 080 figure 2 ). Aortic distensibility was decreased in OSA (p<0.05)(abstract 080 figure 3 ). Although ODI correlated with aortic distensibility (r=−0.35, p<0.01), this association was not significant after adjustment for age and systolic blood pressure. LV mass (p<0.05) and volume (p<0.01) as well as RV mass (p<0.05) - all indexed to body surface area - were increased in OSA (abstract 080 figure 4 ). On multivariate regression analysis, ODI emerged as an independent predictor of LV mass (β=0.41(0.17)(p<0.05)), LV volume (β=0.34(0.16)(p<0.05)) and RV mass (β=0.16(0.07)(p<0.05)) in OSA. PA acceleration time was significantly shortened in OSA (p<0.005)(abstract 080 figure5 ) and significantly correlated with ODI (r=−0.38, p<0.05), RV volume (r=−0.47, p<0.01) and RV mass, even after adjustment for ODI (β=−0.13(0.05)(p<0.05)). Conclusions: OSA is associated with increased atheroma burden and complicated atheromatic lesions. Increased central aortic stiffening, that appears to be dependent on an increase in systolic blood pressure, is detected in OSA. An independent association between OSA and eccentric LV remodelling and hypertrophy is demonstrated by CMR. CMR reveals for the first time an association between the presence and severity OSA and RV hypertrophy, which may be dependent on an concomitant increase in pulmonary arterial pressure.